Comparative enzymology of 11 beta -hydroxysteroid dehydrogenase type 1 from glucocorticoid resistant (Guinea pig) versus sensitive (human) species. - Shafqat, N; Elleby, B; Svensson, S; Shafqat, J; Jörnvall, H; Abrahmsen, L; Oppermann, U (2003)
Type 1 11 beta-hydroxysteroid dehydrogenase constitutes a prereceptor control mechanism through its ability to reduce dehydroglucocorticoids to the receptor ligands cortisol and corticosterone in vivo. We compared kinetic characteristics of the human and guinea pig 11 beta-hydroxysteroid dehydrogenase isozymes derived from species differing in glucocorticoid sensitivity. Both orthologs were successfully expressed as full-length enzymes in yeast and COS7 cells and as soluble transmembrane-deleted constructs in Escherichia coli. Both isozymes display Michaelis-Menten kinetics in intact cells and homogenates and show low apparent micromolar K(m) values in homogenates, which are lowered by approximately one order of magnitude in intact cells, allowing corticosteroid activation at physiological glucocorticoid levels. Recombinant soluble proteins were expressed and purified with high specific dehydrogenase and reductase activities, revealing several hundred-fold higher specificity constants than those reported earlier for the purified native enzyme. Importantly, these purified soluble enzymes also display a hyperbolic dependence of reaction velocity versus substrate concentration in 11-oxoreduction with K(m) values of 0.8 microm (human) and 0.6 microm (guinea pig), close to the values obtained from intact cells. Active site titration was carried out with the human enzyme using a novel inhibitor compound and reveals a fraction of 40-50% active sites/mol total enzyme. The kinetic data obtained argue against the involvement of 11 beta-hydroxysteroid dehydrogenase as a modulating factor for the glucocorticoid resistance observed in guinea pigs. Instead, the expression of 11 beta-hydroxysteroid dehydrogenase type 1 in the Zona glomerulosa of the guinea pig adrenal gland suggests a role of this enzyme in mineralocorticoid synthesis in this hypercortisolic species.